2022
DOI: 10.1039/d1cp05785e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrene formation is the first step of the thermal and photochemical decomposition reactions of organic azides

Abstract: In this work, the decomposition of a prototypical azide, isopropyl azide, both in the ground and excited states, has been investigated through the use of multiconfigurational CASSCF and MS-CASPT2 electronic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 74 publications
(112 reference statements)
1
11
0
2
Order By: Relevance
“…To this end, we have performed ab initio quantum chemical calculations at the CASSCF and MS-CASPT2 levels, which are one of the most appropriate theoretical approximations to deal with this class of molecules and most importantly this type of reactions. 23 26 It will be shown that our work corroborates and explains in detail the assertions and conclusions given by Platz et al, 22 excepting the population of the second excited state of the diazo compound upon irradiation with the 350 nm light. In fact, we will demonstrate that the variation of the reactivity in changing the excitation wavelength is due to the absorption of the intermediate carbene ( EPC ) at 350 nm.…”
Section: Introductionsupporting
confidence: 90%
“…To this end, we have performed ab initio quantum chemical calculations at the CASSCF and MS-CASPT2 levels, which are one of the most appropriate theoretical approximations to deal with this class of molecules and most importantly this type of reactions. 23 26 It will be shown that our work corroborates and explains in detail the assertions and conclusions given by Platz et al, 22 excepting the population of the second excited state of the diazo compound upon irradiation with the 350 nm light. In fact, we will demonstrate that the variation of the reactivity in changing the excitation wavelength is due to the absorption of the intermediate carbene ( EPC ) at 350 nm.…”
Section: Introductionsupporting
confidence: 90%
“…Open shell singlet nitrene 7 cannot be located on the PES at the chosen DFT level and triplet nitrene 7 is 6.2 kcal mol −1 higher in energy than azide 4 , but there is no experimental evidence for its formation, although nitrenes have been experimentally detected in thermal decompositions of organic azides [24] . Note that Peláez and co‐workers reported that the photochemical and thermal decomposition of organic azides is best described through the use of multiconfigurational CASSCF and MS‐CASPT2 electronic structure calculations [25] . Using these methods, the thermal and photochemical decomposition product is an open shell singlet nitrene, which isomerizes in an almost barrierless process to the corresponding imine derivative.…”
Section: Resultsmentioning
confidence: 99%
“…[24] Peláez und Mitarbeiter berichteten, dass die photochemische und thermische Zersetzung organischer Azide und deren elektronische Struktur am besten durch die Verwendung von Multikonfigurationsmethoden, wie CAS-SCF und MS-CASPT2, beschrieben wird. [25] Unter Verwendung dieser Methoden ist das thermische und photochemische Zersetzungsprodukt ein offenschaliges Singulett-Nitren, das in einem nahezu barrierefreien Prozess zum entsprechenden Imin-Derivat isomerisiert. Die geschätzte Obergrenze für die Nitren-Imin-Isomerisierung liegt bei weniger als 1 kcal mol À 1 .…”
Section: Ergebnisse Und Diskussionunclassified